A complete solution to the Cvetković–Rowlinson conjecture. Issue 3 (2nd March 2021) - Lin, Huiqiu; Ning, Bo
Abstract: In 1990, Cvetković and Rowlinson conjectured that among all outerplanar graphs on n vertices, K 1 ∨ P n − 1 attains the maximum spectral radius. In 2017, Tait and Tobin confirmed the conjecture for sufficientlty large values of n . In this article, we show the conjecture is true for all n ≥ 2 except for n = 6 .